2013
DOI: 10.1111/evo.12130
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Viviparity: A Phylogenetic Test of the Cold-Climate Hypothesis in Phrynosomatid Lizards

Abstract: The evolution of viviparity is a key life-history transition in vertebrates, but the selective forces favoring its evolution are not fully understood. With >100 origins of viviparity, squamate reptiles (lizards and snakes) are ideal for addressing this issue. Some evidence from field and laboratory studies supports the "cold-climate" hypothesis, wherein viviparity provides an advantage in cold environments by allowing mothers to maintain higher temperatures for developing embryos. Surprisingly, the cold-climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(141 citation statements)
references
References 86 publications
6
122
3
5
Order By: Relevance
“…The evolution of viviparity in reptiles increased morphological and lineage diversification [7,8,10]. Our study found the opposite pattern: viviparous species exhibited reduced rates of evolution and lower diversification in some life-history traits.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…The evolution of viviparity in reptiles increased morphological and lineage diversification [7,8,10]. Our study found the opposite pattern: viviparous species exhibited reduced rates of evolution and lower diversification in some life-history traits.…”
Section: Discussioncontrasting
confidence: 56%
“…Viviparity has likely evolved independently six times within this North American family [7]. We predicted higher diversification rates in the life histories of viviparous species.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations